2009
DOI: 10.5507/bp.2009.036
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Prevalence of Genes Coding for Enterotoxins, Exfoliatins, Panton-Valentine Leukocidin and TSST-1 Between Methicillin-Resistant and Methicillin-Susceptible Isolates of Staphylococcus Aureus at the University Hospital in Olomouc

Abstract: Aims:Staphylococcus aureus is an important pathogen characterised by its potential to express many virulence factors. Currently, special attention is being paid to methicillin-resistant strains of S. aureus (MRSA). The aim of this study was to compare the prevalence of 13 selected virulence factor genes in methicillin-resistant versus methicillinsusceptible S. aureus (MSSA) isolates and to investigate their accumulation in the same isolate.Methods: Real-time PCR was used to detect the presence of genes in 200 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
34
5
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 30 publications
5
34
5
4
Order By: Relevance
“…Our data on the frequency of sec and sell genes are in agreement with those previously reported [33,43,44]. It is also notable that, in the presence work, sell gene (n = 18) was accompanied by sec gene in 14 agr group I S. aureus cases.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our data on the frequency of sec and sell genes are in agreement with those previously reported [33,43,44]. It is also notable that, in the presence work, sell gene (n = 18) was accompanied by sec gene in 14 agr group I S. aureus cases.…”
Section: Discussionsupporting
confidence: 82%
“…It was not detected by Sila et al, [43]; Peck et al, [48] have reported that seh was more frequently detected in isolates from nasal than from blood specimens; El-Huneidi et al, [49] have reported that this SAg toxin gene was only infrequently detected in clinical isolates of S. aureus from Jordan; Hu et al, [33] have shown that 11/140 MSSA isolates were positive for this toxin gene. Recently, in Kuwait City, Udo et al, [34] reported that staphylococcal enterotoxin gene H was found with a frequency of 21.5% among strains, but not all agr group III S. aureus isolates.…”
Section: Discussionmentioning
confidence: 91%
“…These results agree with those of studies that found lower frequencies of the genes encoding PVL in MSSA clinical isolates (Kuehnert et al 2006), but contrast with data reported from the Czech Republic, where it was found that the lukS/F-PV, tst and sec genes were more frequent in MSSA isolates and enterotoxins genes sea, seb, sed and eta were most prevalent in MRSA strains (Sila et al 2009). Also, in this study, lukS/F-PV were more frequently observed in SCCmec IVc isolates (94%), but they were not restricted to this cassette type and they were also present in SCCmec types I, IVa and V. Other studies conducted in China (Wu et al 2010) and in USA (Abdel-Haq et al 2009) that have evaluated the epidemiological and molecular features of MRSA and MSSA isolates from children found that the most frequent SCCmec type was IVa and all of these strains carried the lukS/F-PV genes.…”
Section: Discussioncontrasting
confidence: 57%
“…For multiplex PCR, the amplification was performed under the following conditions: 94°C for 10 min, followed by 35 cycles of 94°C for 90 s, 49°C for 90 s, and 72°C for 90 s, with a final elongation of 72°C for 10 min. The staphylococcal toxin genes were investigated by PCR as previously described (17,18). The amplification was carried out in the LightCycler 2.0 thermocycler (Roche Applied Science, Germany).…”
Section: Molecular Methodsmentioning
confidence: 99%